Europäische Gesellschaften zwischen Kohäsion und Spaltung Rolle, Herausforderungen und Perspektiven Sozialer Arbeit - Baier, Florian; Borrmann, Stefan; Hefel, Johanna; Thiessen, Barbara (Theorie, Forschung und Praxis der Sozialen Arbeit, 2022)
Promoting and preserving social cohesion has become a central challenge for European societies. Based on contributions from the first trinational conference of DGSA, OGSA and SGSA, this book addresses both the meaning of social cohesion for individuals and societies and the question of how social work can contribute to promoting and preserving social cohesion as the basis of liberal democratic societies.